1972
DOI: 10.1002/j.1556-6978.1972.tb01943.x
|View full text |Cite
|
Sign up to set email alerts
|

Counselor Role, Function, and Job Satisfaction

Abstract: A survey of 246 certified Tennessee school counselors was made regarding job satisfaction as related to the ASCA role and function recommendations. It was found that the counselors were most job satisfied with placement activities and least job satisfied with research activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1976
1976
1983
1983

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…, derive the least satisfaction (Dietz, 1972), and devote the least amount of time (Atkinson, Froman, Romo, & Mayton, 1977;. Wheeler and Loesch (1981) reviewed the literature on program evaluation and concluded that a primary reason for poor counselor response and performance in this area is due to a lack of training.…”
mentioning
confidence: 99%
“…, derive the least satisfaction (Dietz, 1972), and devote the least amount of time (Atkinson, Froman, Romo, & Mayton, 1977;. Wheeler and Loesch (1981) reviewed the literature on program evaluation and concluded that a primary reason for poor counselor response and performance in this area is due to a lack of training.…”
mentioning
confidence: 99%
“…Does the impact of counselor educator become internalized by the practicing school counselor with increasing experience and thus not remain as clearly associated with the formal preparation period or do the objectives and universality of theory and techniques which the school counselor is exposed to in training gain more status as the school counselor is confronted by a greater diversity of student, parental and administrative demands (Herr & Cramer, 1965, P. 8). Dietz (1972) in a Tennessee study asked counselors to rate their job satisfaction in relation to the ten American School Counselors Association's (ASCA) role and function recommendations using a semantic differential instrument. The mean rankings revealed the following, in order of satisfaction, from high to low: placement, public relations, educational-occupational planning, staff consulting, pupil appraisal, referral, counseling, program development and research.…”
Section: Counselor Role Aspectsmentioning
confidence: 99%
“…The role and function of the counselor has come under increasing scrutiny in the last 2 decades (Armor, 1969;Arbuckle, 1972;Carmical & Calvin, 1972). The fiscal austerity of the late 1970s and early 1980s and the attendant demands for accountability have highlighted the need for a clarification of the counselor's role (Buckner, 1975;Dietz, 1972a;Wiggins, 1977). Wells and Ritter (1979) expressed concern, however, that the current crisis in the profession is not being acknowledged by practitioners.…”
mentioning
confidence: 99%